An Overview of Early Development of Mesonephric System in Camels (Camelus dromedarius) with Special Emphasis on Mesonephric Kidney: Structure and Function - Zolain H.B.; Marwa-Babiker A.M.; Hussein F. A.; Elkhair N.M. (Journal of Applied Veterinary Sciences, 2024)
This study aimed to examine the features of the mesonephric system in fourteen (14) dromedary camel fetuses. Standard anatomical, histological, histochemical and scanning electron microscopic procedures were applied to investigate the role of the camel's mesonephros as a secretory system and hematopoietic center. In early development, the mesonephros occupied a large field of the abdominal cavity, expanded by lateral symmetry from the diaphragm to the pelvic cavity in the dorso-sublumbar regions. At 112 days of gestation, the mesonephros regressed at the cranial extremities. In the early stages of development, the mesonephros was enclosed by a thin capsule of mesenchymal connective tissue; irregular mesonephric tubules with large lumens lined with simple cuboidal cells interspersed with tiny blood vessels; and a few hemopoietic cells were discovered near the periphery of the mesonephros. With advanced development, giant glomeruli with a parietal layer lined with a simple columnar epithelium were seen in the ventral and associated boundary between the mesonephros and the developing gonads. Glycogen and alkaline phosphatase elicited an intense response in the capsule, the mesonephric tubule epithelium, renal tubule system, blood vessels, and hemopoietic cells, which was expected and contributed to water conservation and urine concentration. Scanning electron microscopy revealed that the outer surface of the mesonephros had an oval-brain shape. Based on the findings, the camel’s mesonephric system had a secretory function and served as a hematopoietic center. The morphology and development of the camel’s mesonephric system were comparable to those of other mammalian species, however, with unique traits and characteristics.